Answer:
Orbital motion results when the object’s forward motion is balanced by a second object’s gravitational pull.
Explanation:
The gravitational force is responsible for the orbital motion of the planet, satellite, artificial satellite, and other heavenly bodies in outer space.
When an object is applied with a velocity that is equal to the velocity of the orbit at that location, the body continues to move forward. And, this motion is balanced by the gravitational pull of the second object.
The orbiting body experience a centripetal force that is equal to the gravitational force of the second object towards the body.
The velocity of the orbit is given by the relation,
Where
V - velocity of the orbit at a height h from the surface
R - Radius of the second object
G - Gravitational constant
h - height from the surface
The body will be in orbital motion when its kinetic motion is balanced by gravitational force.
Hence, the orbital motion results when the object’s forward motion is balanced by a second object’s gravitational pull.
Answer:
The decrease is due to the bulge at the equator (putting more distance between the rest of the planet and the surface
Explanation:
The ideal gas constant is a proportionality constant that is added to the ideal gas law to account for pressure (P), volume (V), moles of gas (n), and temperature (T) (R). R, the global gas constant, is 8.314 J/K-1 mol-1.
According to the Ideal Gas Law, a gas's pressure, volume, and temperature may all be compared based on its density or mole value.
The Ideal Gas Law has two fundamental formulas.
PV = nRT, PM = dRT.
P = Atmospheric Pressure
V = Liters of Volume
n = Present Gas Mole Number
R = 0.0821atmLmoL K, the Ideal Gas Law Constant.
T = Kelvin-degree temperature
M stands for Molar Mass of the Gas in grams Mol d for Gas Density in gL.
Learn more about Ideal gas law here-
brainly.com/question/28257995
#SPJ4
Answer:
The answer is below
Explanation:
a) The initial velocity (u) = 24 m/s
We can solve this problem using the formula:
v² = u² - 2gh
where v = final velocity, g= acceleration due to gravity = 9.8 m/s², h = height.
At maximum height, the final velocity = 0 m/s
v² = u² - 2gh
0² = 24² - 2(9.8)h
2(9.8)h = 24²
2(9.8)h = 576
19.6h = 576
h = 29.4 m
b) The time taken to reach the maximum height is given as:
v = u - gt
0 = 24 - 9.8t
9.8t = 24
t = 2.45 s
The total time needed for the apple to return to its original position = 2t = 2 * 2.45 = 4.9 s